1999
DOI: 10.1017/s0007485399000255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adult diet on demographic and population parameters of the tropical fruit flyAnastrepha serpentina(Diptera: Tephritidae)

Abstract: The effect of artificial and natural sources of adult food on the survival and reproduction of the tropical fruit fly, Anastrephaserpentina (Wiedemann) was studied. Caged adult flies were exposed during their whole lifespan to water and one of the following diets: sucrose, intact fruit, open fruit, bird faeces, sucrose plus intact fruit, sucrose plus open fruit, sucrose plus yeast hydrolysate, and sucrose plus bird faeces. All flies exposed to intact fruit or bird faeces died within the first five days of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 18 publications
1
48
0
5
Order By: Relevance
“…3). Segundo Jácome et al (1999), as populações de moscas-das-frutas são direcionadas pela combinação simultânea de efeitos, tanto de disponibilidade de recursos alimentares e substratos de oviposição, como de efeitos negativos de fatores de mortalidade como os bióticos e abióticos. Então, a busca por alimento faz com que as moscas invadam os pomares, não só para procurarem sítios de oviposição, como também, para se alimentarem e acasalarem.…”
Section: Resultados E Discussão Flutuação Populacional De Espécies Deunclassified
See 1 more Smart Citation
“…3). Segundo Jácome et al (1999), as populações de moscas-das-frutas são direcionadas pela combinação simultânea de efeitos, tanto de disponibilidade de recursos alimentares e substratos de oviposição, como de efeitos negativos de fatores de mortalidade como os bióticos e abióticos. Então, a busca por alimento faz com que as moscas invadam os pomares, não só para procurarem sítios de oviposição, como também, para se alimentarem e acasalarem.…”
Section: Resultados E Discussão Flutuação Populacional De Espécies Deunclassified
“…Provavelmente isso aconteceu com A. obliqua, o que é justificável por tratarse de espécie polífaga e predominante no Amazonas. A invasão de adultos em épocas sem plantas hospedeiras pode ocorrer em função da procura de alimentos, como foi discutido por Jácome et al (1999). A maior quantidade de moscas foi coletada na época de maior precipitação, registrando-se baixa correlação (r = 0.22, P > 0,05) entre o número de mosca/armadilha.dia (MAD) e a precipitação.…”
Section: Resultados E Discussão Flutuação Populacional De Espécies Deunclassified
“…For some tephritids, ingestion of protein can also affect longevity. Access to protein has been reported to increase longevity in A. serpentina ( Jácome et al , 1999 ), whereas, in C. capitata , the results have been highly variable Maor et al , 2004 ). Recent laboratory studies on fertile and sterile Queensland fruit flies (Tephritidae: Bactrocera tryoni ; 'Q-fly') have found that continuous post-teneral access to a protein source, yeast hydrolysate, can increase mating propensity and longevity in both males and females ( PerezStaples et al , 2007b ).…”
Section: Introductionmentioning
confidence: 99%
“…This result is interesting because according to Heimpel & Rosenheim (1995), a honey fed female will consume a smaller number of immature hosts and consequently there would be an increase in their reproductive success, since this will allow larvae development that could be used for oviposition. Reasons to explain these results are not very clear, we believe that female parasitoids that fed on honey were satiated and as a consequence they change their feeding behavior consuming less eggs and larvae (Jácome et al 1999). Other possibility is that honey in combination with the protein of prepupae and pupae was enough to supply the nutritional requirements of the parasitoid (Jervis & Kidd 1986).…”
Section: Discussionmentioning
confidence: 96%